Effect of Family Caregiver Empowerment on Binge Eating Behavior in Type 2 Diabetes Patients - Rondhianto Rondhianto; Baskoro Setioputro; Agil Agustin (JKG (JURNAL KEPERAWATAN GLOBAL), 2026)
Background: Improper diet arrangements in type 2 diabetes (T2D) patients can cause eating patterns to be disturbed in the form of binge eating behavior. The family can play a helping role in improving diabetes management. One of the interventions that can be given to empower families is the Family Caregiver Empowerment Model (FCEM). This study aimed to analyze the effect of FCEM on binge eating in T2D patients. Methods: This study was a randomized control group pre-test and post-test design with a total sample of 85 respondents taken by cluster random sampling, divided randomly (treatment = 41; control = 44). The independent variable is FCEM, while the dependent variable is binge eating behavior. Data was collected using the Indonesian version of the Binge Eating Scale questionnaire and analyzed used the Wilcoxon sign rank test and independent T-test. Results: There were differences in binge eating behavior in the treatment group before and after intervention (Z= -5.347; p=0.001), whereas in the control group, there was no difference in pre-test and post-test scores (Z= -0.599; p= 0.549). The study result showed that there was a significant difference in the average value between the treatment and control groups (t =5.017; p=0.001). Conclusion: FCEM intervention can reduce binge eating behavior to increase adherence to the diabetes diet program. Nurses can use FCEM intervention to empower family caregiver to help T2D patients improve and maintain eating habits to improve diabetes self-care behaviors.